Febrile Ulceronecrotic Mucha-Habermann Disease: A Case Report and Review of Literature in the Paediatric Population - Jue Liu; Jianbo Zhong; Qiaowei Wang; Yinglian Cai; Jian Chen (Medical Journals Sweden, 2023)
Febrile ulceronecrotic Mucha-Habermann disease (FUMHD) is a rare fulminant variant of pityriasis lichenoides et varioliformis acuta (PLEVA) that is characterized by a large ulceronecrotic appearance with high fever and a variety of systemic symptoms. We report here a case of FUMHD in a 17-year-old male Chinese patient who was treated successfully with a combination therapy of methotrexate, methylprednisolone, and intravenous immunoglobulin. In addition, a literature review was conducted to summarize the key characteristics of paediatric FUMHD cases.